Arthroscopic Foveal Reattachment of the Triangular Fibro Cartilaginous Complex - Kermarrec, Gwénolé; Cohen, Gilles; Upex, Peter; Fontes, Didier (Journal of Wrist Surgery, 2020)
Background Foveal attachment of the triangular fibrocartilaginous complex (TFCC) is essential for distal radioulnar joint stability. Controversy still exists as to which is the best treatment in case of foveal lesions. Actual arthroscopic techniques either require mini open steps or are complex and expensive. We present a simple all inside knotless repair, providing a strong bony fixation in the fovea.Materials and Methods Through 3–4 and 6R portals, the ulnar fovea is debrided and a wire is passed percutaneously through the TFCC to place a mattress suture at its free end. It is then reattached to the fovea with an impacted anchor.Retrospective Study Between 2013 and 2016, a cohort of 5 patients presenting with isolated Palmer 1B, EWAS 2 lesions of the TFCC were operated on with this technique. Clinical evaluation was based on a compared measurement of the grip strength, pain on a visual analogic scale (VAS), different ranges of motion, and distal radioulnar joint (DRUJ) stability. We also used functional scores: Mayo modified wrist score (MMWS), Quick disability arm, shoulder and hand (DASH), and patient-related wrist evaluation (PRWE). The average follow-up was 29.4 months (range 9–42 months).Results On postoperative evaluation, pain was reduced by 5 points (range 1–9) and grip strength averaged 94% of the unaffected side. Range of motion averaged 92% on the unaffected side. DRUJ instability was slight in 4 patients and mild in 1 patient. MMWS was excellent for 1, good for 1, and satisfactory for 3 patients. Quick Dash averaged 17.68 (range 0–38.6) compared with preoperative average of 59.48 (range 45–77) with an amelioration of 43 (range 34–57).PRWE averaged 20 (range 1–41.5) compared with preoperative average of 60.3 (range 33.5–76.5) with an amelioration of 41 (range 32–58). We reported no complications and particularly no lesions of the dorsal sensory branch of the ulnar nerve.Conclusions We present a simple arthroscopic technique using a single suture anchor placed in the ulnar fovea. Repairs performed with this technique are simple and the results achieved seem to be similar to those obtained with conventional open or arthroscopic techniques, although further investigation with an increased number of patients and follow-up are required. It however became our first choice of treatment in European Wrist Arthroscopy Society (EWAS) 2 lesions of the TFCC.
Keywords: wrist arthroscopy; TFCC; foveal